Oblicz wartość wyrażenia:

(2x-3y)(2x+3y)-(x-3y)²-x(5x-y)-7xy

dla:
x = √2
y= 1/√3

mi wyszło tak:

4x² + 6xy - 6xy - 9y² + x² - 6xy +9y² -5x² + xy -7xy
po redukcji wyrazów podobnych

4x²+ x² - 6xy -5x² + xy - 7xy

po podstawieniu

8 + 2 - 6√2/√3 - 10 + √2/√3 - 7√2/√3 =
-5√2/√3 - -7√2/√3 = -12√2/√3 * √3/√3 = -12√6/3 = -4√6

2

Odpowiedzi

2010-03-03T20:00:46+01:00
(2x-3y)(2x+3y)-(x-3y)²-x(5x-y)-7xy=
=4x²-9y²-(x²-6xy+9y²)-5x²+xy-7xy=
=4x²-9y²-x²+6xy-9y²-5x²+xy-7xy=
=-2x²-18y²

x = √2
y= 1/√3

-2x²-18y²=-2*(√2)²-18*(1/√3)²=-2*2-18*(1/3)=-4-6=-10
  • hhh
  • Rozwiązujący
2010-03-03T20:14:20+01:00
Niestety nie podoba mi się Twoje rozwiązanie.

(2x-3y)(2x+3y)-(x-3y)²-x(5x-y)-7xy=4x²-9y²-(x²-6xy+9y²)-(5x²-xy)-7xy=
4x²-9y²-x²+6xy-9y²-5x²+xy-7xy=-2x²-18y²

dla:
x = √2
y= 1/√3

-2*(√2)²-18*(1/√3)²=-2*2-18*1/3=-4-6=-10